Bibliophobia the end and the beginning of the book - Cummings, Brian (Clarendon lectures in English, 2022)
"Bibliophobia is a personal meditation on the 5000-year history of writing and of books, from the perspective of the smartphone. Its starting point is the contemporary idea of "the death of the book", embodied not only in the replacement of the physical book by digital media, but in the accompanying twenty-first century experience of paranoia and of literary apocalypse. It traces a twin fear of omniscience and oblivion right back to the origins of writing in ancient Sumeria and Egypt, and then forwards to the age of Google. It covers examples of bibliophobia from the first Chinese emperor to Nazi Germany, alongside a parallel story of bibliomania and bibliolatry within world religions and literatures. Using examples from six continents, it discusses topics such as the origins and decipherment of different kinds of human script; the development of textual media such as scrolls, codices, printed books, and artificial intelligence; the collection and destruction of libraries; the use of books as holy objects, talismans, and shrines; and the history of slavery, heresy, blasphemy, censorship and persecution. Originating as the Clarendon Lectures in the Faculty of English at the University of Oxford, the methods of Bibliophobia range across book history; comparative religion; philosophy from Plato to Hegel and Freud; and a wide range of global literature from ancient to contemporary. Richly illustrated with manuscripts, printed objects, and art works, at its heart is the power that books always (and continue to) have in the emotional, spiritual, bodily, and imaginative life of readers"--Provided by publisher.